Pap Smear Examination as a Strategy for Prevention and Early Detection of Cervical Cancer at the HKBP Jatisampurna Church, Bekasi - Marliana Nurprilinda; Frisca Ronauli Batubara; Fajar Lamhot Gultom; Abitmer Gultom (International Journal of Community Service (IJCS), 2026)
Cervical cancer remains one of the leading causes of morbidity and mortality among women, particularly in developing countries, largely due to late diagnosis and low participation in early screening programs. Limited knowledge and awareness regarding cervical cancer and Pap smear examinations contribute significantly to delayed detection. This community service activity aimed to increase the knowledge and awareness of the congregation of HKBP Jatisampurna Church, Bekasi, regarding the importance of early detection of cervical cancer through Pap smear examinations. The activity was conducted using interactive educational counseling followed by free Pap smear examination services. Educational sessions covered cervical cancer risk factors, prevention strategies, and the procedures and benefits of Pap smear screening. A total of 50 female congregation members participated in the activity and voluntarily underwent Pap smear examinations. The results demonstrated an improvement in participants’ knowledge and understanding of cervical cancer and the importance of early detection through Pap smear screening. In addition, there was an increased willingness and participation of congregation members in undergoing Pap smear examinations, indicating positive behavioral changes toward preventive health practices. In conclusion, educational counseling combined with direct Pap smear services effectively increased awareness and participation in cervical cancer screening among the HKBP Jatisampurna Church congregation. This community service activity represents a strategic approach to cervical cancer prevention and early detection and highlights the importance of community-based interventions in promoting women’s reproductive health